2013
DOI: 10.1002/ajh.23552
|View full text |Cite
|
Sign up to set email alerts
|

Darbepoetin‐alfa and intravenous iron administration after autologous hematopoietic stem cell transplantation: A prospective multicenter randomized trial

Abstract: We conducted a randomized study analyzing the impact of darbepoetin alfa (DA) administration with or without intravenous (i.v.) iron on erythroid recovery after autologous hematopoietic cell transplantation (HCT). Patients were randomized between no DA (Arm 1), DA 300 μg every 2 weeks starting on Day 28 after HCT (Arm 2), or DA plus i.v. iron 200 mg on Days 28, 42, and 56 (Arm 3). The proportion achieving complete hemoglobin (Hb) response within 18 weeks (primary end point) was 21% in Arm 1 (n = 24), 79% in Ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 35 publications
0
34
0
2
Order By: Relevance
“…Therefore, we decided to investigate the long-term kinetics of hepcidin after HCT in a group of patients participating in a clinical trial of post-transplant DA with and without intravenous iron therapy. 8 In our study, hepcidin levels prior to HCT were not increased compared to healthy controls.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 58%
“…Therefore, we decided to investigate the long-term kinetics of hepcidin after HCT in a group of patients participating in a clinical trial of post-transplant DA with and without intravenous iron therapy. 8 In our study, hepcidin levels prior to HCT were not increased compared to healthy controls.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 58%
“…ESAs mainly reduce transfusion requirements and improve quality of life. [36][37][38][39][40] Predictors of response to ESAs include the ratio of observed to expected Hb (<0.9) and the preserved BM function, reflected by the platelet counts (>150x10 9 /L). 33,38,41 A systematic review of the use of ESAs in more than 20,000 cancer patients confirmed that their use reduced the relative risk of transfusions due to increase of erythroid responses, but there was evidence that ESAs increased mortality during ESA administration and thus decreased OS.…”
Section: Regimens Neutropenia (%) Vte (%) Pn (%) Infection (%) Spm (%)mentioning
confidence: 99%
“…In multiple myeloma or lymphoma patients after autologous hematopoietic cell transplantation, supplementation of darbepoetin-a with IS (200 mg iron on days 28, 42 and 56 post-transplant) increased the percentage of patients with Hb increase ‡ 2 g/dl from 88 to 100% and reduced the median time to response from 28 to 25 days (p = 0.0231) compared to no iron supplementation [63]. The percentage of patients requiring RBC transfusions and the cumulative darbepoetin-alfa dose were significantly lower in the IS arm (0 vs 11.1%; p = 0.0276 and 1210 vs 1440 µg; p = 0.015, respectively).…”
Section: Oncologymentioning
confidence: 99%